The Association between Type 2 Diabetes Mellitus and Thyroid Cancer - Young-Gyun Seo; Ho-Chun Choi; Ah Reum An; Do Joon Park; Young Joo Park; Kyu Eun Lee; Sue K. Park; Yunji Hwang; Belong Cho (Journal of Diabetes Research)
Aim. The incidence of thyroid cancer is increasing worldwide. The prevalence of type 2 diabetes mellitus (T2DM) is also increasing. Therefore, we aimed to analyze the effect of T2DM on thyroid cancer. Methods. A case-control study was performed. A total of 415 healthy controls with thyroid ultrasound screening and physician consultation were selected from the Thyroid Cancer Longitudinal Study (T-CALOS). Among patients with thyroid cancer who were enrolled in T-CALOS, 415 patients were matched to the control group according to age and sex. We assessed the effects of T2DM, T2DM duration, and T2DM medication on thyroid cancer. Results. Women with T2DM had lower odds of thyroid cancer than women without T2DM (odds ratio [OR]: 0.40, 95% confidence interval [CI]: 0.20–0.81). Individuals receiving T2DM medication had higher odds of thyroid cancer compared to those without T2DM medication (OR: 5.21, 95% CI: 1.58–17.15). Individuals with T2DM duration <6 years had lower odds of thyroid cancer compared to those without T2DM (OR: 0.58, 95% CI: 0.34–0.97). Conclusions. Individuals with early T2DM are presumed to have a low incidence of thyroid cancer, and this effect seems to last up to 6 years after diagnosis of T2DM.